In Memoriam – Professor Witold Gutkowski - Błachowski, Bartłomiej; Hołobut, Paweł (Computer Assisted Methods in Engineering and Science, 2020)
Professor Witold Gutkowski, our doctoral advisor, teacher, and mentor for many years, passed away suddenly on 18 November 2019 at the age of 91. Professor Gutkowski remained an active researcher until his death. We will remember him as a man full of kindness, composure and wisdom, who devoted his life to serving his homeland, and as a distinguished scholar who greatly contributed to high-quality scientific research.